P223 Influence of ambient air pollution on RA disease activity scores. (20th April 2020) - Alsaber, Ahmad R; Pan, Jiazhu; Al-Herz, Adeeba; Alkandary, Dhary S; Al-Hurban, Adeeba; Setiya, Parul; Group, KRRD RA Study
Abstract: Background: This study aims to estimate the influence of air pollution ambients using the Air Quality Index (AQI) to Rheumatoid Arthritis (RA) disease activity. Disease Activity Score with 28 examined joints (DAS-28) and Clinical Disease Activity Index (CDAI) considered as disease activity indices for RA patients in the state of Kuwait. Methods: Data for patients with RA disease were collected from Kuwait Registry for Rheumatic Diseases (KRRD) from 2013 to 2017. Moreover, data on air pollution obtained from The Kuwait Environmental Public Authority (K-EPA) during the same period. Statistical analysis was conducted using STATA to highlight the significant association between study variables. Descriptive statistics, correlation analysis and linear regression model techniques were employed to estimate the significant associations between RA disease activity represented by DAS-28 and CDAI; with air pollution components (PM10, NO2, SO2, O3, and CO). Multiple Imputation by Chained Equations (MICE) algorithm was also employed to tackle the value of the missing data for air pollution data. Results: Total of 9, 875 patients visits included in the analysis that matching with air pollution information from K-EPA database according to date and patient living address governorate. The study found SO2 and NO2 were significantly associated with RA disease activity using DAS-28 index, also, for CDAI index as well. For the score of RA disease activity using DAS-28 index, the correlation results show a positive significant correlation with exposure of SO2 using AQI (rp = 0.07), also the same results with the with the exposure of NO2 using AQI (rp = 0.07). The final model is demonstrating the effect from air-pollutants gaseous with RA factors (Swollen, RF, anti-CCP, ESR, CRP) on RA disease activity. The AQI of NO2 and SO2 still showed positive associations with disease activity performance of RA. The linear regression model shows a positive effects of NO2 (beta = 0.003, 95% CI: 0.002-0.005) and (beta = 0.048, 95% CI: 0.030-0.066) for DAS-28 and CDAI respectively, where for SO2, the results shows positive significant effect with (beta = 0.003, 95% CI: 0.0004-0.005) and (beta = 0.044, 95% CI: 0.018-0.070) for DAS-28 and CDAI respectively. Conclusion: In conclusion, our study showed that air ambients were significantly correlated to RA disease activity scores and should be considered as a possible risk factor for RA activity. Disclosures: A.R. Alsaber None. J. Pan None. A. Al-Herz None. D.S. Alkandary None. A. Al-Hurban None. P. Setiya None.